The protective effects of Ghrelin/GHSR on hippocampal neurogenesis in CUMS mice. (1st September 2019) - Huang, Hui-Jie; Chen, Xiao-Rong; Han, Qiu-Qin; Wang, Jing; Pilot, Adam; Yu, Rui; Liu, Qiong; Li, Bing; Wu, Gen-Cheng; Wang, Yan-Qing; Yu, Jin
Abstract: Ghrelin is an orexigenic hormone that also plays an important role in mood disorders. Our previous studies demonstrated that ghrelin administration could protect against depression-like behaviors of chronic unpredictable mild stress (CUMS) in rodents. However, the mechanism related to the effect of ghrelin on CUMS mice has yet to be revealed. This article shows that ghrelin (5 nmol/kg/day for 2 weeks, i.p.) decreased depression-like behaviors induced by CUMS and increased hippocampal integrity (neurogenesis and spine density) measured via Ki67, 5-bromo-2-deoxyuridine (BrdU), doublecortin (DCX) labeling and Golgi-cox staining, which were decreased under CUMS. The behavioral phenotypes of Growth hormone secretagogue receptor (Ghsr) -null and wild type (WT) mice were evaluated under no stress condition and after CUMS exposure to determine the effect of Ghsr knockout on the behavioral phenotypes and stress susceptibility of mice. Ghsr -null mice exhibited depression-like behaviors under no stress condition. CUMS induced similar depression- and anxiety-like behavioral manifestations in both Ghsr -null and WT mice. A similar pattern of behavioral changes was observed after hippocampal GHSR knockdown. Additionally, both Ghsr knockout as well as CUMS exhibited deleterious effects on neurogenesis and spine density in the dentate gyrus (DG). Besides, CCK8 assay and 5-Ethynyl-2′-deoxyuridine (EdU) incorporation assay showed that ghrelin has a proliferative effect on primary cultured hippocampal neural stem cells (NSCs) and this proliferation was blocked by D-Lys3-GHRP-6 (DLS, the antagonist of GHSR, 100 μM) pretreatment. Ghrelin-induced proliferation is associated with the inhibition of G1 arrest, and this inhibition was blocked by LY294002 (specific inhibitor of PI3K, 20 μM). Furthermore, the in vivo data displayed that LY294002 (50 nmol, i.c.v.) can significantly block the antidepressant-like action of exogenous ghrelin treatment. All these results suggest that ghrelin/GHSR signaling maintains the integrity of hippocampus and has an inherent neuroprotective effect whether facing stress or not. Highlights: Ghsr knockout and CUMS induced depression-like phenotype independently Ghrelin promoted hippocampal neurogenesis in CUMS mice Ghrelin promoted the proliferation of hippocampal NSCs might by inhibiting the G1 arrest The protection of ghrelin against CUMS relied on the PI3K/Akt pathway.